IMPLICIT AND EXPLICIT LINGUO-AXIOLOGICAL AND LINGUO-PRAGMATIC MARKERS OF THE CATEGORY “HEALTHY LIFESTYLE” IN GERMAN ADVERTISING DISCOURSE IN THE FIRST THIRD OF THE 20TH CENTURY - Petruk, Vasyl (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2026)
This article examines implicit and explicit linguo-axiological and linguo-pragmatic markers of the category “healthy lifestyle” in German advertising discourse of the first third of the 20th century. An analysis is conducted of explicit lexical markers (gesund, kräftigend, rein – healthy, strengthening, pure) and implicit pragmatic strategies used to establish an associative link between a specific product and health, and subsequently between a citizen’s health and their benefit to the state and the nation. It has been established that the comprehensive combination of these markers in advertising texts ensured effective persuasion and contributed to the formation of a positive image of the product. A lexical-semantic analysis of German advertising texts in print publications from the 1900s to the 1930s was conducted, and the frequency of use of explicit and implicit groups of markers in these texts, as well as their interaction in the context of achieving the pragmatic goals of advertising, was investigated.